(untitled) (ASEAN Engineering Journal, 2022)
This paper aims to reduce the power losses by improving the hydrophobic strength of ceramic insulators for densely industrialized coastal areas to save them from flashover due to contamination. The hydrophobic strength of ceramic insulators must increase to resolve the contamination occurrence and power losses problem. The system progresses by creating an artificial chamber to provide five different environmental conditions heat, rain, fog, dust, and humidity. The testing part of the system includes taking readings for rain happened, temperature, humidity, and pH for five years using data from reliable sources and creating acidic rain, temperature, dust, and fog artificially to obtain results more accurately. The Coating includes nitrocellulose material dissolved in a solvent mixture of diacetone alcohol, Hexa hydro phenol, ethyl acetate, benzol, and toluene in a spray form to apply on the insulators. The coated insulator was tested in an artificial aging chamber by applying all the environmental effects of the coastal areas for five years using accelerated testing. After performing tests, the results show a 7% decrease in contamination development on the ceramic insulator surface. Hence improving its hydrophobic strength and losses of the power system minimized.